Position Analysis and Strategic Recommendations for Business Improvement in The Micro-Small Industry of Oil Palm Post-Harvest Equipment in Kampar Regency, Riau Province - Juarsa, Rahmadini Payla; Sangadah, Hanik Atus (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2023)
AbstractMany industries producing post-harvest oil palm equipment are growing in Riau Province, Indonesia because this province has a large area of oil palm plantations. Micro-small businesses dominate this industry. The micro-small oil palm post-harvest equipment industry experiences many obstacles in improving and developing its business. This research aims to analyze the position of the micro-small oil palm post-harvest equipment industry and then provide strategic recommendations to improve their business. The position analysis used is Business Model Canvas (BMC) analysis and Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. Business development strategy recommendations use the Strengths, Weaknesses, Opportunities, Threats (SWOT), and Quantitative Strategic Planning Matrix (QSPM) methods. The research results show that the company is in a growth and development phase. The top two strategies recommended for these companies are maximizing marketing channels and good cooperation through cooperatives, oil palm processing companies (such as PTPN), government agencies, and social media, and improving product quality by providing skilled human resources and research and development activities.Keywords: business development strategy, micro-small industry, oil palm post-harvest equipment, position analysis AbstrakAreal perkebunan kelapa sawit yang luas di Provinsi Riau mengakibatkan industri yang memproduksi alat pasca panen kelapa sawit banyak tumbuh di provinsi ini. Industri ini didominasi oleh usaha skala mikro hingga skala kecil. Industri alat pasca panen kelapa sawit skala mikro dan kecil ini mengalami banyak kendala dalam peningkatan dan pengembangan usahanya. Tujuan penelitian ini adalah menganalisis posisi industri mikro dan kecil alat pascapanen kelapa sawit kemudian memberikan rekomendasi strategi untuk meningkatkan usahanya. Analisis posisi yang digunakan adalah analisis Business Model Canvas (BMC) dan matriks Internal Factor Evaluation (IFE) dan External Factor Evaluation (EFE). Rekomendasi strategi pengembangan bisnis dilakukan dengan metode Strengths, Weaknesses, Opportunities, Threats (SWOT) dan Quantitative Strategic Planning Matrix (QSPM). Hasil penelitian menunjukkan bahwa perusahaan berada pada fase pertumbuhan dan perkembangan. Dua strategi teratas yang direkomendasikan untuk perusahaan tersebut adalah memaksimalkan saluran pemasaran dan kerjasama yang baik melalui koperasi, perusahaan pengolah kelapa sawit (seperti PTPN), instansi pemerintah, dan media sosial, meningkatkan kualitas produk melalui pemenuhan sumber daya manusia yang terampil, dan kegiatan penelitian pengembangan.Kata kunci: alat pascapanen kelapa sawit, analisis posisi, industri mikro dan kecil, strategi pengembangan usaha